2019
DOI: 10.1177/1460408619885505
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality in major trauma patients in Trinidad and Tobago – A view from the developing world

Abstract: Increased age, blunt trauma, ISS≥25 and increasing RTS were factors found to be associated with increased risk of mortality in major trauma patients in Trinidad and Tobago. The TRISS model in this study was found to be an excellent discriminator between those who had a high chance of survival to those who had a low probability of survival. A multi-center trial is required for validation of trauma prediction tools such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…A 2017 Trinidad study at a rural emergency department found that “the median door-to-ECG time was 10 min, with 52.5% of patients achieving a door-to-ECG time of less than 10 min. The median door-to-needle time was 70 minutes, with only 8.2% of patients having a door-to-needle time of less than 30 minutes” [ 38 ]. In 2019, among AMI patients, 57.5% of patients received thrombolysis within 30 min [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…A 2017 Trinidad study at a rural emergency department found that “the median door-to-ECG time was 10 min, with 52.5% of patients achieving a door-to-ECG time of less than 10 min. The median door-to-needle time was 70 minutes, with only 8.2% of patients having a door-to-needle time of less than 30 minutes” [ 38 ]. In 2019, among AMI patients, 57.5% of patients received thrombolysis within 30 min [ 14 ].…”
Section: Reviewmentioning
confidence: 99%